Development of Spike Receptor-Binding Domain Nanoparticles as a Vaccine Candidate against SARS-CoV-2 Infection in Ferrets - Young-Il Kim (American Society for Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a causative agent of the CoV disease 2019 (COVID-19) pandemic, enters host cells via the interaction of its receptor-binding domain (RBD) of the spike protein with host angiotensin-converting enzyme 2 (ACE2). Therefore, the RBD is a promising vaccine target to induce protective immunity against SARS-CoV-2 infection.